2004
DOI: 10.3354/meps274001
|View full text |Cite
|
Sign up to set email alerts
|

Protein model for pollutant uptake and elimination by living organisms and its implications for ecotoxicology

Abstract: The conceptual model on which chemical assessment of pollutants is based is flawed. The assumption in ecotoxicology -that pollutants cross the biological membrane only by passive diffusion of their solute phase (diffusion model) and thus, that only water-soluble pollutants are biologically available -is inconsistent with the biologists' understanding of the role and functioning of the biological membrane. The biological membrane both isolates organisms, cells and organelles from their external environments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 133 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…The utilization of S. spallanzanii mucus to extract bioactive substances of pharmaceutical interest is encouraged also on the basis of the results obtained on lipids as well as PCB concentrations. Notably lipids are related to bioaccumulation of lipophilic pollutants, including PCBs, in living substrates (Jones & de Voogt, 1999; Quinnell et al , 2004; Brown & Bythell, 2005; Ritchie, 2006); the low value in lipid content within the mucus of S. spallanzanii indicated the low probability of accumulation of persistent lipophilic pollutants. In addition, the estimated PCB content is below the maximum accepted value of contamination in pharmaceutical preparations (<0.005 µg g −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of S. spallanzanii mucus to extract bioactive substances of pharmaceutical interest is encouraged also on the basis of the results obtained on lipids as well as PCB concentrations. Notably lipids are related to bioaccumulation of lipophilic pollutants, including PCBs, in living substrates (Jones & de Voogt, 1999; Quinnell et al , 2004; Brown & Bythell, 2005; Ritchie, 2006); the low value in lipid content within the mucus of S. spallanzanii indicated the low probability of accumulation of persistent lipophilic pollutants. In addition, the estimated PCB content is below the maximum accepted value of contamination in pharmaceutical preparations (<0.005 µg g −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…they do not always consider exposure content and biological uptake. This can potentially lead to an underestimation of toxicities, as suggested by Quinnell et al (2004). We found that an uptake of only 2 pg EE2 induces significant reduction in embryo viability in a species that is often exposed continuously to EE2 in their surrounding water.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, fish ecotoxicology studies often focus only on the effects of constant concentrations of chemical compounds in the water (OECD, 1992, Leet et al, 2011, Aris et al, 2014, but see Bjerregaard et al (2008) and Knudsen et al (2011). However, determining both, exposure content and individual uptake, is necessary to better understand the toxicity of a substance (Quinnell et al, 2004, Skillman et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Methylmercury is a global pollutant with known neurotoxic and reproductive effects, and exposure occurs mainly through the diet. It binds to sulfur amino acids during uptake, storage, and elimination in aquatic organisms (Quinnell et al ) including phytoplankton, bacteria, and fish (Lawson and Mason ; Leaner and Mason ; Schaefer and Morel ), varies among taxa (e.g., Clayden et al ), biomagnifies through aquatic food webs (Clayden et al ), and has been shown to be almost exclusively present as methylmercury‐cysteine in fish muscle proteins (Harris et al ; Lemes and Wang ). In aquatic invertebrates, speciation (or chemical form) of methylmercury has not been determined; however, more than 85% of the selenium, a metalloid with similar properties to mercury, was bound to the amino acids methionine (MET) and cysteine (CYS) (Andrahennadi et al ), the two sulfur‐containing amino acids of proteins.…”
mentioning
confidence: 99%